Updated international recommendations (EULAR, 2023) for the treatment of psoriatic arthritis - Yu. L. Korsakova; T. V. Korotaeva; Sh. Erdes; E. Yu. Loginova; E. L. Nasonov (Научно-практическая ревматология, 2024)
In recent years, there has been significant progress in the study of psoriatic arthritis (PsA). The possibilities of psoriasis (Ps) and PsA therapy have expanded. The following drugs are used for the treatment of PsA: conventional synthetic disease-modifying antirheumatic drugs (DMARDs); biological DMARDs targeting tumour necrosis factor (TNF), interleukin (IL) 12/23 or IL-23 pathway, and IL-17A and IL-17A/F pathway; and targeted synthetic DMARDs that inhibit Janus kinases or phosphodiesterase 4. There have been changes since the last EULAR (European Alliance of Associations for Rheumatology) recommendations for the treatment of PsA from 2019, so an update was required, which examines the treatment of the entire spectrum of PsA manifestations, including cutaneous Ps, extra-musculoskeletal manifestations and concomitant diseases. The updated recommendations include 7 general principles and 11 recommendations. The article presents the EULAR recommendations for the treatment of PsA, as well as research agenda indicating priorities for future research in PsA. The updated recommendations should be useful not only for clinicians, but also for patients when discussing treatment options and making decisions.